Developmental anomalies of the female genital tract from classifications to diagnosis: current issue state - L.V. Adamya; E.V. Sibirskaya; L.G. Pivazyan; Y.D. Davydova; V.A. Tarlakyan (LCC «Medicine-Inform», 2023)
L.V. Adamyan1,2, E.V. Sibirskaya1,3,4, L.G. Pivazyan2, Y.D. Davydova5, V.A. Tarlakyan5 1A.I. Yevdokimov Moscow State University of Medicine and Dentistry, Moscow, Russian Federation 2V.I. Kulakov National Medical Research Center for Obstetrics, Gynecology and Perinatology, Moscow, Russian Federation 3Pirogov Russian National Research Medical University, Moscow, Russian Federation 4Republican Children's Clinical Hospital, the Branch of N.I. Pirogov Russian National Research Medical University, Moscow, Russian Federation 5I.M. Sechenov First Moscow State Medical University (Sechenov University), Moscow, Russian Federation Congenital anomalies (malformations) of the female genital tract are persistent intrauterine deviations from norm variations of size, shape, proportions, symmetry, topography and organogenesis, resulting in their function disorder. Congenital anomalies of the female genital tract account for 14% of all congenital malformations and 3-7% of gynecological disorders in children and adolescents. Currently, there are a number of unresolved issues related to the systematization and diagnosis of such anomalies. The article presents an up-to-date and carefully selected information on this topic and highlights existing difficulties that require further study. The literature review is aimed at searching for relevant classifications and modern diagnostics for congenital anomalies of the female genital tract for further personalized treatment tactics. Literature analysis has shown that the etiology and pathogenesis of congenital anomalies of the female genital tract are complex, heterogeneous and understudied. To date, there is no single generally accepted classification of congenital anomalies of the female genital tract, while the proposed article presents modern methods for diagnosing this pathology and the subtleties concerning the results interpreting for a correct diagnosis. Keywords: congenital anomalies, developmental anomalies of the female genital tract, classification, diagnosis. For citation: Adamyan L.V., Sibirskaya E.V., Pivazyan L.G., Davydova Y.D., Tarlakyan V.A. Developmental anomalies of the female genital tract from classifications to diagnosis: current issue state. Russian Journal of Woman and Child Health. 2023;6(4):425-432 (in Russ.). DOI: 10.32364/2618-8430-2023-6-4-16.